Comparative Dissolution Study of Metoprolol Tartrate Loaded PLGA (50:50) and PLGA (75:25) Microparticles - Rasool, Fatima; Ahmad, Mahmood; Muhammad Shoaib Khan, Haji; Ali Khan, Shujaat; Murtaza, Ghulam (Asian Journal of Chemistry, 2011)
To prepare and evaluate comparatively the dissolution behaviour of metoprolol tartrate loaded PLGA (50:50) and PLGA (75:25) microparticles. Metoprolol tartrate loaded PLGA microparticles were prepared using non-solvent addition phase separation technique with drug to polymer ratio 1:1, 1:2 and 1:3. Metoprolol tartrate contents were determined spectrophotometrically at 273 nm. Drug-polymer compatibility was determined by FTIR, XRD and thermal analysis. Microparticle morphology was characterized by SEM. In vitro dissolution studies for microparticles were performed in phosphate buffer pH 7.2 and the samples were analyzed by HPLC with UV detector operated at 273 nm. Mean particle size range was 15-65 μm for both grades of PLGA. The encapsulation efficiency range was 60-88 % in various formulations. Biphasic release phenomenon was observed with an initial fats release phase and subsequently a continuous and slower release thereafter. The non-solvent addition process led to formation of porous, spherical and discrete metoprolol tartrate microparticles with PLGA. The microparticles with PLGA 75:25 exhibited more sustained release of drug than those of with PLGA 50:50. Similarly in vitro release of drug was also affected by polymer concentration. FTIR, XRD and DSC results showed no drug-polymer chemical interaction during the microencapsulation except slight modification of drug particle behaviour from crystalline to amorphous behaviour.